Immune Polarization Potential of the S. aureus Virulence Factors SplB and GlpQ and Modulation by Adjuvants - Mrochen, Daniel M.; Trübe, Patricia; Jorde, Ilka; Domanska, Grazyna; Brandt, Cindy van den; Bröker, Barbara M. (Frontiers in Immunology, 2021)
Protection against Staphylococcus aureus is determined by the polarization of the anti-bacterial immune effector mechanisms. Virulence factors of S. aureus can modulate these and induce differently polarized immune responses in a single individual. We proposed that this may be due to intrinsic properties of the bacterial proteins. To test this idea, we selected two virulence factors, the serine protease-like protein B (SplB) and the glycerophosphoryl diester phosphodiesterase (GlpQ). In humans naturally exposed to S. aureus, SplB induces a type 2-biased adaptive immune response, whereas GlpQ elicits type 1/ type 3 immunity. We injected the recombinant bacterial antigens into the peritoneum of S. aureus-naïve C57BL/6N mice and analyzed the immune response. This was skewed by SplB toward a Th2 profile including specific IgE, whereas GlpQ was weakly immunogenic. To elucidate the influence of adjuvants on the proteins’ polarization potential, we studied Montanide ISA 71 VG and ImjectTMAlum, which promote a Th1 and Th2 response, respectively. Alum strongly increased antibody production to the Th2-polarizing protein SplB, but did not affect the response to GlpQ. Montanide enhanced the antibody production to both S. aureus virulence factors. Montanide also augmented the inflammation in general, whereas Alum had little effect on the cellular immune response. The adjuvants did not override the polarization potential of the S. aureus proteins on the adaptive immune response.